Penerapan Strategi Pembelajaran Snowball Throwing untuk Meningkatkan Hasil Belajar Matematika Pada Materi Kubus dan Balok - Lilik Nur Susilowati; Moh. Syadidul Itqan; Hariyanto (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to improve the mathematics learning outcomes of grade IX students of MTsN 1 Probolinggo on the material of cubes and cuboids through the application of the Snowball Throwing learning strategy. This study is a Classroom Action Research (CAR) which is carried out in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects were 29 students with a Minimum Completion Criteria (KKM) of 75. Data collection techniques used learning outcome tests, observation, and documentation. The results of the study showed a significant increase in student learning outcomes. The average student score at the initial stage was 68.93 with a completeness of 58.62%. After the application of the Snowball Throwing strategy in cycle I, the average score increased to 89.48 with a completeness of 86.21%. In cycle II, the average score reached 95.52 with a classical completeness of 100%. These results indicate that the Snowball Throwing learning strategy is effective in improving students' mathematics learning outcomes on the material of cubes and cuboids.